Determinasi Likuiditas dan Good Corporate Governance Terhadap Nilai Perusahaan: Studi Literature - Moridu, Irwan; Cakranegara, Pandu Adi; Siddiqa, Heidi; Azizi, Muhammad; Ahmad, Srifatmawati (Jurnal Manajemen, 2023)
Liquidity is related to the company's ability to meet the company's financial needs in the short term with current funds in the company, and good corporate governance is a system that functions to regulate how the company is managed and controlled properly. When liquidity management and implementation of good corporate governance system are carried out by the company well, it will increase the value of the company. With a good company value, it will be able to attract investors and can provide welfare to the owners and shareholders of the company. Therefore, this article aims to determine the effect of liquidity management applied by the company and the good corporate governance system that is implemented to increase the value of the company. The method used in this study is a qualitative method in the form of a literature study in the field of financial management by paying attention to liquidity and system good. corporate governance on firm value. The method of writing scientific articles is by using qualitative methods and literature studies or Library Research. The results of the analysis and review of literature explain that liquidity management by the company has a positive effect on firm value. The good corporate governance system implemented by the company has an impact on the company's value which is getting better